EXPERIMENTAL DETERMINATION OF ELASTICITY MODULE AND POISSON’S RATIO OF TAMPING STONE DEPENDING ONCOMPOSITION AND TYPE OF FILLER - Тынына, Сергей; Чоботько, Игорь; Яцун, Артур; Рыбалко, Игорь (SWorldJournal, 2021)
Abstract. The paper represents results of the research making it possible to apply dynamic modulus Еdnm for Еstc evaluation. Equations of correlative relationship between Еstc and Еdnm result from the correlation analysis of the data of static and dynamic